Same-Sex Marriage and Civil Law Consequences: A Comparative Study of Indonesia and Thailand - Raisya Alya Najla; Nurhilmiyah Nurhilmiyah (JURNAL USM LAW REVIEW, 2026)
This study aims to analyze and compare the legal regulation of same-sex marriage in Indonesia and Thailand and to examine its juridical implications for civil status and civil law consequences. The issue has become increasingly significant due to divergent national legal frameworks within ASEAN and growing cross-border mobility, which creates potential legal uncertainty regarding marital status recognition and the protection of civil rights. This research employs normative legal methods using statutory and comparative law approaches, based on the analysis of legislation, constitutional provisions, and relevant legal doctrines. The results show that Indonesia does not recognize same-sex marriage because marital validity is fundamentally based on religious law, resulting in the absence of civil law consequences, including marital status recognition, joint property rights, inheritance rights, and parental authority. Conversely, Thailand legally recognizes same-sex marriage through amendments to its Civil and Commercial Code, granting same-sex couples full civil rights and legal protection equivalent to heterosexual spouses. This difference reflects contrasting legal paradigms, where Indonesia emphasizes religious legitimacy as the foundation of marriage, while Thailand prioritizes civil equality and legal certainty. The novelty of this study lies in its comparative analysis of civil law consequences within ASEAN’s plural legal systems. This research contributes to comparative family law scholarship and highlights the potential for transnational legal conflicts arising from inconsistent marital recognition across jurisdictions.